Stability Analysis of a T-S Prey-Predator Model with Disease in both Species using Fuzzy Impulsive Control - Kaladhar, K.; Singh, Khushbu (Journal of Environmental Accounting and Management, 2026)
The objective of this paper is to investigate the dynamical behavior of a prey-predator system in which disease infection is in both the prey and predator populations. Prey and Predators are divided into two categories - the susceptible and the infected. The Lotka-Volterra predator-prey system’s stability is investigated using the Takagi-Sugeno (T-S) impulsive control model and the Fuzzy impulsive control model. A system of four differential equations has been proposed and analyzed. The Takagi-Sugeno (T-S) impulsive control model and the fuzzy impulsive control model are used to explore the stability of the Lotka-Volterra predator-prey system. Numerical simulation provides the global stabilities and the fuzzy solution.